P60 Simple measures to improve TB control: applying the cohort review process in London. (2nd December 2011) - White, J; Anderson, C; Dart, S; Tamne, S; deKoningh, J; Hemming, S; Anderson, S; Abubakar, I; Lipman, M
Abstract : Despite much recent effort, there has been little change in national rates of tuberculosis (TB). Outside of the UK, the brief, structured review of the management, contact investigation and outcome of each TB case during their treatment (cohort review, CR) has improved TB control. North Central London (NCL) TB Service has piloted this approach. To date, 525 subjects with active TB have been discussed at four cohort reviews. Each "cohort" of patients were reviewed 6–9 months from start of treatment. A single case is usually reviewed within 3 min. Here we compare key outcomes relating to case management and contact tracing between an NCL TB population notified and treated prior to CR (Quarter 3 2009, n=158) and following CR implementation (Quarter 3, 2010, 1 year from start, n=125). Treatment completion rates rose (82%–90%). The proportion of cases lost to follow-up reduced (2.5%–0%). The proportion of smear positive pulmonary cases with at least one risk factor on Directly Observed Therapy increased from 42% to 67%. Uptake of HIV testing rose (71%–89%). The proportion of pulmonary TB cases with at least 1 and >5 contacts identified both increased (64%–84% and 50%–67%, respectively). In conclusion, within a short space of time cohort review has led to an improved index case management and contact tracing process in our service. It improves accountability, enhances patient management and facilitates staff education. Accurate, comprehensive and prompt data underpin this success. If this is sustained, we believe that cohort review will result in improved patient outcomes. It provides, also, an excellent structure within which advances such as the National Strain Typing project may be introduced to achieve maximal clinical impact.